KAJIAN TINGKAT PENCEMARAN UDARA OLEH GAS NH3 DAN H2S PADA PROSES PENGOMPOSAN SECARA AEROB - Setiyo, Yohanes (Universitas Udayana, 2007)
This research objective was to know the level polutan of NH3and H2S from aerobic composting process. Modified Briski method was use to identification NH3 and H2S. Pada metode Briski et al. (2003) tidak ada pengukuran gas NH3 and H2S. Both polutan were colect at solvent BaCL2 and H2SO4 0.1 N along one week, than the level of concentration at air were identificated by chromatography method. The level concentration of NH3 at the air was 0.092 ppm to 0.25 ppm, and the level polutan of H2S to the air was 0.3 ppm to 1.1 ppm. Both polutan were below from standard of SNI.